The Angiotensin-Melatonin Axis - Luciana A. Campos; Jose Cipolla-Neto; Fernanda G. Amaral; Lisete C. Michelini; Michael Bader; Ovidiu C. Baltatu (International Journal of Hypertension)
Accumulating evidence indicates that various biological and neuroendocrine circadian rhythms may be disrupted in cardiovascular and metabolic disorders. These circadian alterations may contribute to the progression of disease. Our studies direct to an important role of angiotensin II and melatonin in the modulation of circadian rhythms. The brain renin-angiotensin system (RAS) may modulate melatonin synthesis, a hormone with well-established roles in regulating circadian rhythms. Angiotensin production in the central nervous system may not only influence hypertension but also appears to affect the circadian rhythm of blood pressure. Drugs acting on RAS have been proven effective in the treatment of cardiovascular and metabolic disorders including hypertension and diabetes mellitus (DM). On the other hand, since melatonin is capable of ameliorating metabolic abnormalities in DM and insulin resistance, the beneficial effects of RAS blockade could be improved through combined RAS blocker and melatonin therapy. Contemporary research is evidencing the existence of specific clock genes forming central and peripheral clocks governing circadian rhythms. Further research on the interaction between these two neurohormones and the clock genes governing circadian clocks may progress our understanding on the pathophysiology of disease with possible impact on chronotherapeutic strategies.